URGENSI PEMBIASAAN PUASA SENIN KAMIS TERHADAP PEMBENTUKAN KARAKTER ISLAMI SANTRI DI PONDOK PESANTREN AL FATICH SURABAYA - Ma’arif, Ahmad Miftahul; Ahsantudhonni (MIYAH : Jurnal Studi Islam, 2023)
Abstract: This research is related to the problem of the habit of fasting on Mondays and Thursdays towards the formation of Islamic character in accordance with religious teachings, which is not only character formation that is important and instilled in humans but needs improvement after character formation. Because considering the many young people who play a major role in the progress of changing times and so as not to fall into this rapid flow of globalization. The focus of the problem based on the background that has been written above, namely: (1) What is the form of character that is applied in the habit of fasting on Mondays and Thursdays at the Al Fatich Islamic Boarding School, Surabaya? (2) What is the process of character building through fasting at the Al Fatich Islamic Boarding School, Surabaya. The research method used in this writing uses a qualitative approach which collects data using observation, interview and documentation methods. Data obtained from Islamic boarding school caretakers, administrators, and students as informants in this study. The results of the study show that: First, the form of character that is applied in the habit of fasting on Monday and Thursday is described in daily life in accordance with religious teachings. Second, in the process of character formation, it describes the stages in forming character through fasting based on character values. Keywords: Habit, Fasting Monday Thursday, Islamic Character.